Do Firms Respond to Peer Disclosures? Evidence from Disclosures of Clinical Trial Results - Capkun, Vedran; Lou, Yun; Otto, Clemens A.; Wang, Yin (The Accounting Review, 2023)
ABSTRACT Using data on the registration of clinical trials and the disclosure of trial results, we examine how firms respond to peer disclosures. We find that firms are less likely to disclose their own trial results if the results of a larger number of closely related trials are disclosed by their peers. This relation is stronger if the firms face higher competition (as measured by the number of competing trials). It is weaker if the firms are further along in their research than the peers (as measured by the trials’ phase) and if the peers’ disclosures convey more negative news (as measured by the firms’ stock price reaction). We also find that firms are more likely to abandon ongoing trials if a larger number of peers disclose the results of closely related trials. Additional tests suggest that this real effects channel does not drive the impact on the firms’ disclosure decisions. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: M4.